2015
DOI: 10.1007/s12010-014-1451-8
|View full text |Cite
|
Sign up to set email alerts
|

Production of Lactic Acid from the Mixture of Softwood Pre-hydrolysate and Paper Mill Sludge by Simultaneous Saccharification and Fermentation

Abstract: Paper mill sludge is a solid waste material composed of pulp residues and ash generated from pulping and paper making process. The carbohydrate portion of the sludges from Kraft/Recycle paper mill has chemical and physical characteristics similar to those of commercial wood pulp. Because of its high carbohydrate content and well-dispersed structure, the sludge can be biologically converted to value-added products without pretreatment. In bioconversion of solid feedstock such as paper mill sludge, a certain amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 47 publications
(22 citation statements)
references
References 22 publications
0
22
0
Order By: Relevance
“…It might be produced due to softwood hydrolysis and fermentation of cellulose components of the wood. Several workers (Reddy and Yang, 2005; Shi et al, 2015) have reported the presence of lactic acid in pulp and paper mill effluents after bacterial degradation. Benzoic acid (benzoate) was also detected in biostimulated effluent after 3 and 6 days of bacterial growth.…”
Section: Discussionmentioning
confidence: 99%
“…It might be produced due to softwood hydrolysis and fermentation of cellulose components of the wood. Several workers (Reddy and Yang, 2005; Shi et al, 2015) have reported the presence of lactic acid in pulp and paper mill effluents after bacterial degradation. Benzoic acid (benzoate) was also detected in biostimulated effluent after 3 and 6 days of bacterial growth.…”
Section: Discussionmentioning
confidence: 99%
“…The integrated ‘biorefinery’ process to produce biofuels and chemicals as a supplementary unit in kraft paper mills is an intriguing possibility . Our previous research found that the production of various chemicals could be integrated into the kraft process, while still preserving the main products ‐ paper and pulp . However, the biggest bottleneck in this biorefinery process is the high cost of the enzymes for the hydrolysis step .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, few natural LAB can ferment inexpensive feedstocks such as starch, and no native cellulolytic and/or hemicellulolytic LAB has been isolated so far (Okano, Tanaka, et al, ). Fermentation of enzymatically hydrolyzed lignocellulosic feedstocks by LAB has been reported (Hu et al, ; Shi, Kang, & Lee, ). However, the high cost of commercial cellulases significantly reduces economic advantage of using cheap raw materials (Okano, Tanaka, et al, ; Olson, McBride, Shaw, & Lynd, ).…”
Section: Introductionmentioning
confidence: 99%